Extração e caracterização de nanocristais de celulose a partir de casca de soja, e sua aplicação como agente de reforço em nanocompósitos poliméricos utilizando carboximetilcelulose como matriz - Flauzino Neto, Wilson Pires (2012)
Given the problems involved in plastic recycling and the dwindling exhaustion of fossil resources, there is a great interest in sustainable and environmentally friendly materials. In this context, the application of cellulose nanocrystals (NC) as reinforcement in polymer matrixes has attracted considerable attention in this field since NC based nanocomposites generally exhibit significant improvements in thermal, mechanical, and barrier properties compared to the neat polymer or conventional composites, and additionally it offers environmental benefits. Soy hull is an agro-industrial waste available in large quantities in several countries, including Brazil, which deserves to be better and/or properly used. In this study, NC were extracted and characterized from soy hulls under different conditions of acid hydrolysis in order to evaluate their suitability as a reinforcement agent for the manufacture of nanocomposites. The hydrolysis was performed at 40 °C for 30 or 40 min, using 30 mL of H2SO4 64% for each gram of fiber. The NC of soy hulls (NCC) were labeled NCC30 or NCC40 depending on the hydrolysis time. To evaluate the reinforcement capability of NC obtained were produced nanocomposite films using carboxymethylcellulose (CMC) as polymeric matrix, and evaluated the tensile at break of these films at different load levels. The results showed that a longer extraction time (40 min) resulted in a shorter length of CN and caused some damage on the crystalline structure of cellulose. The NCC30 showed needleshaped, high crystallinity (73.5%), good thermal stability (initial temperature of thermal degradation around 170 °C), average length of 122,7 ± 39,4 nm, diameter of 2,77 ± 0,67 nm and aspect ratio around 44. By the tensile strength tests of the composites was observed that the NCC30 have a greater capability than the reinforcing NCC40. The NCC30 are reinforcing agents satisfactory for the CMC, because there was an increase in tensile at break of the polymer of 2,56 times (or 256%). The NCC produced have a great potential for use as reinforcing agents for the production of nanocomposites and are an alternative which could expand the commercial applications of CMC films. Through the production of cellulose nanocrystals of soy hulls in this work was added value to a plant biomass residue that comes from an agro-industrial commodity.